2011
DOI: 10.1002/jobm.201000342
|View full text |Cite
|
Sign up to set email alerts
|

Root colonization of a rice growth promoting strain of Enterobacter cloacae

Abstract: Enterobacter cloacae GS1 was isolated by in-planta enrichment of a rice rhizoplane bacterial community. It displayed strong seed adherence ability (2.5 × 10(5) cfu/seed) and colonized rice roots reaching up to 1.65 × 10(9) cfu/g of fresh root weight in a gnotobiotic root colonization system. E. cloacae GS1 was motile, able to solubilize tricalcium phosphate, and produced indole acetic acid like substances (15 μg/ml). As an introduced bioinoculant in non-sterile soil, E. cloacae GS1 colonized rice roots and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 28 publications
4
19
0
1
Order By: Relevance
“…Any NAHL-based cross talk between SdiA-containing bacteria and NAHL-producing microbial populations remains to be explored. Earlier, we have shown that Enterobacter cloacae GS1, a plant growth-promoting bacterium, colonizes rice roots as microcolonies and forms biofilm-like structures on the root surface (15). Here, we report that E. cloacae GS1 lacks a functional NAHL-based QS system but harbors the luxR homolog sdiA.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Any NAHL-based cross talk between SdiA-containing bacteria and NAHL-producing microbial populations remains to be explored. Earlier, we have shown that Enterobacter cloacae GS1, a plant growth-promoting bacterium, colonizes rice roots as microcolonies and forms biofilm-like structures on the root surface (15). Here, we report that E. cloacae GS1 lacks a functional NAHL-based QS system but harbors the luxR homolog sdiA.…”
mentioning
confidence: 82%
“…Rice root colonization assay. The colonization abilities of E. cloacae GS1 and its sdiA mutant were studied as described earlier (15). In brief, gnotobiotic rice plants grown in nutrient solution at 25 Ϯ 1°C were inoculated with ϳ10…”
Section: Methodsmentioning
confidence: 99%
“…In rice crops, significant increases in the growth of shoots and roots were observed in plants inoculated with strains of Burkholderia (Estrada et al, 2013;Souza et al, 2013), Enterobacter (Habibi et al, 2014;Shankar et al, 2011), Paenibacillus (Bal et al, 2013;Beneduzi et al, 2008) and Pseudomonas (Habibi et al, 2014;Lavakush et al, 2014;Yasmin et al, 2004). However, only two of these previous studies (Estrada et al, 2013;Lavakush et al, 2014) evaluated the contribution of phosphate solubilisation to the growth and nutrition of rice in pots with non-sterile soil.…”
Section: Discussionmentioning
confidence: 92%
“…An important method for increasing the utilisation efficiency of RPs and/or reducing the use of SPs fertilisers is the use of bacteria that solubilise inorganic phosphates and could potentially increase the amount of P available to plants (Estrada et al, 2013;Lavakush et al, 2014;Oliveira-Longatti et al, 2013Pereira and Castro, 2014;Shankar et al,. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This strain has been deposited in the Microbial Type Collection Centre, Chandigarh, India, with the accession number MTCC 5698. Earlier, we have shown that E. cloacae GS1 outcompetes other innate microbial flora, colonizes rice roots, and promotes plant growth (6). We sequenced the genome of E. cloacae GS1 to gain a better understanding of the genes involved in rhizosphere colonization.…”
mentioning
confidence: 99%